2020
DOI: 10.1371/journal.pone.0243661
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic representation decision theory: How probabilities and values are entangled dual characteristics in cognitive processes

Abstract: Humans are notoriously bad at understanding probabilities, exhibiting a host of biases and distortions that are context dependent. This has serious consequences on how we assess risks and make decisions. Several theories have been developed to replace the normative rational expectation theory at the foundation of economics. These approaches essentially assume that (subjective) probabilities weight multiplicatively the utilities of the alternatives offered to the decision maker, although evidence suggest that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 74 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…13,17,18 This is because subjective risk estimation is also influenced by the importance of the event. 19 The emotional and professional consequences of failing to predict a mortality weigh heavily on surgeons' judgment, which cause them to attribute more weight to worst-case scenarios. A 2020 systematic review by Dilaver et al 18 found that surgeons overestimate mortality risk but are more accurate in predicting morbidity, the latter arguably having a less consequential impact than the former.…”
Section: Discussionmentioning
confidence: 99%
“…13,17,18 This is because subjective risk estimation is also influenced by the importance of the event. 19 The emotional and professional consequences of failing to predict a mortality weigh heavily on surgeons' judgment, which cause them to attribute more weight to worst-case scenarios. A 2020 systematic review by Dilaver et al 18 found that surgeons overestimate mortality risk but are more accurate in predicting morbidity, the latter arguably having a less consequential impact than the former.…”
Section: Discussionmentioning
confidence: 99%
“…As our present focus is on preferential choice under uncertainty, we will summarize how decision field theory (DFT, [ 6 ]) works. Also, given that some of the results we present here rely on insights from stochastic representation decision theory (SRDT, [ 7 ]), we will give a short account of it.…”
Section: Review Of Two Branches Of Decision Modelsmentioning
confidence: 99%
“…In our first analysis, we choose the unbiased parameter configuration ξ = 0, η = 0. [7]), where the inverse double-S-shaped subjective probability arises through the interplay of value-distortion (probability of an event influenced by its magnitude) and time pressure. The model here does not need value distortion, but assumes that the underlying stochastic process is quantum in nature, thus with intrinsic interference between different positions along the deliberation paths.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations